Allium covered metal stent for treatment of malignant ureteral obstruction - Qing, Jing; Hu, Ke; Zhang, Xuan; Luo, Huaming; Chen, Jiangchuan; Li, Changlong; Zhang, Jiamo (Frontiers in Surgery, 2024)
BackgroundMalignant ureteral obstruction (MUO) has the potential to result in a range of outcomes, including varying degrees of hydronephrosis and renal impairment. Allium covered metal stents have provided a new, highly effective treatment option for MUO. Our objective was to evaluate the safety and efficacy of the Allium covered metallic stent for the treatment of malignant ureteral obstruction.MethodsClinical data of 29 patients who underwent endoscopic insertion of an Allium ureteral stent between October 2019 and August 2021 at Yongchuan Hospital, affiliated with Chongqing Medical University, were analyzed retrospectively. At one, three, six and 12 months after insertion, serum creatinine was measured, the width of the renal pelvis was rechecked under ultrasound guidance, and the position and shape of the stent were checked by abdominal x-ray. Data on long-term stent patency, incidence of complications, changes in renal function and hydronephrosis grade were collected and analyzed. Ureteral stent symptom questionnaire (USSQ) was administered preoperatively and after six months in 22 patients with previous stent history.ResultsAllium covered metal stents (n = 33) were implanted successfully in 29 patients who were followed for three to 22 months, with 32/33 stents remaining patent. Serum creatinine levels decreased in 17 patients (p < 0.001), and hydronephrosis decreased in 24 patients. Clavien-Dindo grade I complications were observed in seven patients, Clavien-Dindo II in one patient, whereas stent displacement and stent encrustation occurred in one patient each (Clavien-Dindo III–IV). USSQ scores had significantly improved six months after stent insertion (p < 0.001).ConclusionsAllium ureteral stents are a safe and effective treatment option for malignant ureteral obstruction, with good long-term patency, helping to preserve renal function and improve quality of life.